Transformation and roles of inherent mineral matter in direct coal liquefaction: A mini-review. (1st June 2017) - Li, Wen; Bai, Zong-Qing; Bai, Jin; Li, Xiao
Highlights: Transformation and roles of inherent mineral matter in DCL are briefly overviewed. Pretreatment methods of low-rank coals to enhance the oil yields are proposed. Challenges in investigating transformation and roles of inherent mineral matter in DCL. Abstract: Since direct coal liquefaction (DCL) was invented, it has been a promising technology for the efficient utilization of coal resources and the mitigation of the oil crisis. Generally, coals are regarded as mixtures composed of organic matter and mineral matter. The mineral matter content and nature of coal is highly variable and has been proved to significantly influence the thermal behavior of coals in DCL. Therefore, a clear and comprehensive understanding of the transformation and roles of inherent mineral matter in DCL process is really necessary for guiding the oil yield enhancement and moderating the reaction conditions. After direct liquefaction, the mineral matter would be enriched in the residues. Investigations on transformation and roles of inherent mineral matter can be beneficial for the efficient utilization of the residues as well. In view of the great importance of mineral matter to DCL, this paper briefly summarizes the research progress on the transformation and roles of inherent mineral matter in DCL process, and especially focuses on the major mineral matter in coals. As suitable feedstocks for DCL, the low-rank coals are typically rich in exchangeable metallic species (a kind of mineral matter) which can reduce the oil yield in DCL, hence a detailed discussion of transformation and roles of exchangeable metallic species in DCL is given here and two pretreatment methods of low-rank coals to enhance their oil yields are also proposed.